Proses Adopsi Inovasi Pupuk Cair Organik (Biofish) Berbahan Dasar Ikan Laut pada Komoditas Padi di Kecamatan Muncar Kabupaten Banyuwangi - Hendra Darusalam; Lenny Widjayanthi; Sri Subekti (Kanal: Jurnal Ilmu Komunikasi, 2017)
The organic fertilizer is a fertilizer which made from organic materials, most of the materials used are from plants, land animals and sea animals (fish), so that the fertilizer produced in the form of solid or liquid. One of the organic liquid which produced with fish is biofish. The adoption of organic liquid biofish fertilizer becomes one of farmers' efforts to increase rice planting production. This study aims are to analyze descriptively about knowledge, attitude, decision, implementation and confirmation about organic liquid biofish fertilizer. The determination of area in this research is using purposive method. The location decided for this research is in Muncar Sub-district of Banyuwangi Regency. The research method uses qualitative approach. The method of determining key informant is using Purposive Sampling. The methods of data collection are using interviews, observations, and documents. The data analysis methods are going to be analyzed by reduction, display, conclusion drawing / verification. The method of data validity uses source triangulation. The results showed that farmers' knowledge of biofuel organic fertilizer is good, the farmers are happy and they also like using organic biofertilizer, the farmers receive innovative organic biofuel fertilizer. Although, sometimes they still stop applying and reusing it, but most of farmers will apply organic biofuels continuously because they totally know the benefits of organic biofuels on rice planting.